Preservative prospect of Ugni candollei (Barnéoud) O.Berg, an underexploited edible berry tree from Chile - Rui Fang; Gabin Bitchagno; Max Cui; Paula Coates; James Venison; Andrew Peplow; Debbie Mulligan; Monique S.J. Simmonds (Phytochemistry, 2026)

Modelling Nature-Based Solutions in HEC-RAS - Ramtin Sabeti; Thomas Rodding Kjeldsen; Matt Chambers; Hamed Moftakhari; Luis Partida; Ioanna Stamataki; Solomon Simmonds; Rebecca Lee; Barry Hankin; Melissa Hoskings; Katherine Dixon; James Molloy; et al. (Water Resources Management, 2026)
Nature-based solutions (NBS) are becoming increasingly popular for mitigating flood risk while providing multiple benefits such as enhanced biodiversity, and improved water quality. Hydraulic modelling is an essential tool for evaluating and optimising the flood risk regulating service of NBS. Yet, there is no standardised approach to represent NBS interventions in hydraulic models, leading to inconsistent implementations. This study reports a systematic review of 1,080 publications from Scopus and Web of Science. A final selection of 30 key-studies is identified utilising HEC-RAS to model NBS interventions. By collating and synthesising the various approaches documented in these studies, a consolidated resource for researchers and practitioners is provided. This synthesis offers practical recommendations for the application of different NBS interventions in hydraulic modelling and outlines the corresponding parameter ranges to consider. A critical assessment is undertaken on how these interventions map to specific parameters in the governing hydraulic equations, elucidating the physical mechanisms of flow attenuation and water storage that are broadly applicable to all hydraulic models. To demonstrate the real-world utility of these recommendations, a case study of the River Chew catchment (England) is presented, detailing pre- and post-intervention configurations wherein multiple candidate areas are converted to wetland and woodland using a HEC-RAS 2D model; this section is available in the Supplementary Material. Graphical Abstract

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Communicating the true challenges of saving species: response to Wiedenfeld et al. - James E. M. Watson; Jeremy S. Simmonds; Michelle Ward; Chuan J. Yong; April E. Reside; Hugh P. Possingham; Andrew Rogers; Josie Carwardine (Conservation Biology, 2022)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

A composite measure of habitat loss for entire assemblages of species - Jeremy S. Simmonds; James E. M. Watson; Alvaro Salazar; Martine Maron (Conservation Biology, 2019)
Habitat destruction is among the greatest threats facing biodiversity, and it affects common and threatened species alike. However, metrics for communicating its impacts typically overlook the nonthreatened component of assemblages. This risks the loss of habitat going unreported for species that comprise the majority of assemblages. We adapted a widely used measure for summarizing researcher output (the h index) to provide a metric that describes natural habitat loss for entire assemblages, inclusive of threatened and nonthreatened species. For each of 447 Australian native terrestrial bird species, we combined information on their association with broad vegetation groups with distributional range maps to identify the difference between the estimated pre‐European and current extents of potential habitat, defined as vegetation groups most closely associated with each species. From this, we calculated the loss index (LI), which revealed that 30% of native birds have each lost at least 30% of their potential natural habitat (LI = 30). At the subcontinental scale, LIs ranged from 15 in arid Australia to 61 in the highly transformed southeastern part of the country. Different subcomponents of the assemblage had different LI values. For example, Australia's parrots ( n = 52 species) had an LI of 38, whereas raptors ( n = 32 species) had an LI of 25. The LI is simple to calculate and can be determined using readily available spatial information on species distributions, native vegetation associations, and human impacts on natural land cover. This metric, including the curves used to deduce it, could complement other biodiversity indices if it is used for regional and global biodiversity assessments that compare the status of natural habitat extent for assemblages within and among nations, monitor changes through time, and forecast future changes to guide strategic land‐use planning. The LI is an intuitive tool that can be used to summarize and communicate how human actions affect whole assemblages, not just threatened species.

Gene editing and mutagenesis reveal inter-cultivar differences and additivity in the contribution of TaGW2 homoeologues to grain size and weight in wheat - Wei Wang; James Simmonds; Qianli Pan; Dwight Davidson; Fei He; Abdulhamit Battal; Alina Akhunova; Harold N. Trick; Cristobal Uauy; Eduard Akhunov (Theoretical and Applied Genetics, 2018)

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

A splice acceptor site mutation in TaGW2-A1 increases thousand grain weight in tetraploid and hexaploid wheat through wider and longer grains - James Simmonds; Peter Scott; Jemima Brinton; Teresa C. Mestre; Max Bush; Alicia del Blanco; Jorge Dubcovsky; Cristobal Uauy (Theoretical and Applied Genetics, 2016)

Atmospheric impacts of Arctic sea-ice loss, 1979–2009: separating forced change from atmospheric internal variability - James A. Screen; Clara Deser; Ian Simmonds; Robert Tomas (Climate Dynamics, 2014)

Location of genes for common bunt resistance in the European winter wheat cv. Trintella - Veronika Dumalasová; James Simmonds; Pavel Bartoš; John Snape (Euphytica, 2012)

Declining summer snowfall in the Arctic: causes, impacts and feedbacks - James A. Screen; Ian Simmonds (Climate Dynamics, 2012)

Meta-QTL analysis of the genetic control of ear emergence in elite European winter wheat germplasm - Simon Griffiths; James Simmonds; Michelle Leverington; Yingkun Wang; Lesley Fish; Liz Sayers; Leodie Alibert; Simon Orford; Luzie Wingen; Laurence Herry; Sebastien Faure; David Laurie; et al. (Theoretical and Applied Genetics, 2009)

Genetic mapping of a new flowering time gene on chromosome 3B of wheat - Kateřina Pánková; Zbyněk Milec; James Simmonds; Michelle Leverington-Waite; Lesley Fish; John W. Snape (Euphytica, 2008)

pORE: a modular binary vector series suited for both monocot and dicot plant transformation - Catherine Coutu; James Brandle; Dan Brown; Kirk Brown; Brian Miki; John Simmonds; Dwayne D. Hegedus (Transgenic Research, 2007)

Southern hemisphere cyclones and anticyclones: recent trends and links with decadal variability in the Pacific Ocean - Alexandre Bernardes Pezza; Ian Simmonds; James A. Renwick (International Journal of Climatology, 2007)
The aim of this paper is to study the association between the extratropical Southern Hemisphere and the decadal variability in the Pacific Ocean (PO). We discuss a pattern of coherent large‐scale anomalies and trends in cyclone and anticyclone behaviour in light of the climate variability in the PO over the ERA40 reanalysis period (1957–2002). The two representative PO indices are the Pacific Decadal and Interdecadal Oscillations (PDO and IPO), and here the PDO is chosen owing to it being less associated with the southern oscillation index (SOI). Composites of the indicators of the density and intensity of cyclones/anticyclones given by an automatic tracking scheme were calculated for the years when the PDOI was more than one standard deviation above or below its mean. Although the ERA40 is not free from noise and assimilation changes, the results show a large‐scale feature, which seems to be robust and agrees with earlier studies using different data sets. The sea‐level pressure shows a strong annular structure related to the PDO, which is not seen for the SOI, with lower pressure around Antarctica during the positive phase and vice versa. More intense (and fewer) cyclones and anticyclones were observed during the positive PDO. This is less consistent for the SOI, particularly during the summer when a different PDO/SOI pattern arises at high latitudes. The trends project a pattern coincident with the positive PDO phase and seem to be linked with the main climate shift in the late seventies. Trends observed over the Tasman Sea are consistent with declining winter rainfall over southeastern Australia. Most patterns are statistically significant and seem robust, but random changes in ENSO may play a part, to a certain degree, in modulating the results, and a physical mechanism of causality has not been demonstrated. Although global warming and related changes in the Southern Annular Mode (SAM) may also help explain the observed behaviour, the large‐scale response presented here provides a new insight and would be of considerable interest for further modelling studies. Copyright © 2007 Royal Meteorological Society

Dissecting gene × environmental effects on wheat yields via QTL and physiological analysis - John. W. Snape; M. John Foulkes; James Simmonds; Michelle Leverington; Lesley J Fish; Yingkun Wang; Matteo Ciavarrella (Euphytica, 2007)